Improving interactions of transition-age peers with visual impairment and intellectual disability. (January 2022) - Bruce, Susan; Stutzman, Brent; Nannemann, Allison; Lewitus, Amanda; McDonald, Colleen; Mango, Talia
This collaborative action research study addressed the interaction skills of two young adults with visual impairments and intellectual disability in the context of a board game. The intervention involved the use of an adapted board game, four social stories, and rehearsal of game play skills in the context of individual and group therapy sessions. Instructional strategies included clear within and between activity routines, least to most prompting system, sufficient wait time, and modeling of game play behaviors. Both young men improved their initiation skills, terminated interactions appropriately with fewer prompts, and learned some of the elements of board game play. Self-stimulation and anxiety over changes in their daily lives impacted progress. More research is needed to investigate the potential benefit of social stories for students with visual impairments and additional disabilities.